UJI AKTIFITAS ANTIKANKER EKSTRAK ETANOL KULIT BATANG Bruguiera gymnorhiza TERHADAP SEL MEYLOMA - Warsinah Warsinah; Puji Lestari; Trisnowati Trisnowati (Molekul, 2007)
Mangrove vegetation especially tanjang (Bruguiera gymnorhiza) known as a kind of plant that used as an ingredients for traditional medicine. Bioactive compound in tanjang bark has potential medical. Although there is no previous experiment about tanjang bark, few compounds from Bruguiera genus has been experimented and has an activity as an anti-cancer and anti-tumor. The purpose of this experiment is to conduct sitotoxicity tanjang bark against Meyloma cell. Tanjang bark sample that used obtained from Tritih beach at Cilacap. Tanjang bark that has been cleaned and dried is cut and then crused until it obtain powder. The powder is been maceration with 96% ethanol and been evaporation. The extract that obtain is used in sitotoxicity test using MTT (3-(4,5-dimethylthiazoil-2-il)-2,5-diphenil tetrazolium bromide) method toward Meyloma cell after 24 hour of incubation using several concentration variation. Tanjang bark extract in ethanol has LC50 value 508.19 mg/ml. Morphology analyze and nuclear staining shows that there is apoptosis activity even in small amount. The result shows that tanjang bark extract has a potency as an anti-cancer toward Meyloma cell.